PENDAMPINGAN KEPADA PETANI DESA LINGGA KABUPATEN KARO TERKAIT POTENSI WORTEL SEBAGAI TANAMAN PANGAN - Mikha Meilinda Christina; Twin Yoshua R. Destyanto; Indah Sepwina Putri (As-Sidanah, 2023)
Lingga Village, located in the highlands of Karo Regency, has many kinds of fresh vegetables, and one of the most demanding is the carrot. However, the problem faced by the farmer is that they need more knowledge about the management process, such as the fluctuation of carrot sales prices, the malformation of carrot growth, limited marketing opportunities, and training about it. Therefore, this community service aimed to assist these farmers in finding possible solutions using the ABCD (Asset-Based Community Development) method. The main topic delivered was handling price fluctuations in carrots; preventing the malformation of carrot growth; carrot business potential; and e-commerce-based business development. The results show that the owner still needed to start using the exact formula for the fertilizer composition. Therefore, the team gave the suggestion based on the Ministry of Agriculture’s recommendation. Some potential ways to expand the business suggestion are consignment with traders/conventional shops/supermarkets or even selling the product through e-commerce platforms. However, the owner has limitations in using technology and needs help from relatives, especially the youths. To conclude, the owner should start the expansion with the WhatsApp business because that platform that has been widely used and is easier to maintain.